2017
DOI: 10.3354/meps11811
|View full text |Cite
|
Sign up to set email alerts
|

Nearshore exposure to Deepwater Horizon oil

Abstract: The Deepwater Horizon (DWH) oil spill affected more than 2000 km of shoreline. DWH oil entered the nearshore environment, stranding on shorelines as tar balls and/or emulsified oil, or forming submerged oil mats and integrating into nearshore sediments. The available chemistry data showed submerged sediments, especially within the first 50 m from oiled shorelines, displayed patchy distributions of elevated polycyclic aromatic hydrocarbon (PAH) concentrations in excess of ambient concentrations, which were quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…The results of studies presented in the present Theme Section as well as other studies on the DWHOS encompass the documentation of lethal and sublethal effects of oil spills on individual taxa (see Baker et al 2017), spanning the full range of trophic levels from microbes (Dubinsky et al 2013) to marine mammals (Barron 2012, Schwacke et al 2014). Although many nearshore studies showed localized impacts of the DWHOS, not all nearshore studies indicated negative responses of key species (see Fodrie et al 2014).…”
Section: Nearshore Studies Of Injury From the Dwhosmentioning
confidence: 99%
See 4 more Smart Citations
“…The results of studies presented in the present Theme Section as well as other studies on the DWHOS encompass the documentation of lethal and sublethal effects of oil spills on individual taxa (see Baker et al 2017), spanning the full range of trophic levels from microbes (Dubinsky et al 2013) to marine mammals (Barron 2012, Schwacke et al 2014). Although many nearshore studies showed localized impacts of the DWHOS, not all nearshore studies indicated negative responses of key species (see Fodrie et al 2014).…”
Section: Nearshore Studies Of Injury From the Dwhosmentioning
confidence: 99%
“…Burns & Teal 1979, Fleeger & Chandler 1983, DeLaune et al 1984. Although prior studies allow for general predictions on the direction of species responses, the elucidation of injury pathways, quantification of injuries (Baker et al 2017, this Theme Section) and scaling of restoration (Peterson & Lipcius 2003) -all of which are necessary components of the Natural Resource Damage Assessment (NRDA) process -represented a fundamental challenge to marine ecologists investigating the DWHOS.…”
Section: Response Of Nearshore Ecosystems To Thementioning
confidence: 99%
See 3 more Smart Citations